INVESTIGATING THE RELATIONSHIPS BETWEEN TEACHERS’ READINESS AND THE IMPLEMENTATION OF CHANGE IN ACADEMIC INSTITUTION: A POST-COVID TEACHING AND LEARNING - Noraini Mohd Noor; Ahmad Mujahideen Haji Yusoff (Journal of Islamic, Social, Economics and Development, 2024)
This study aimed to investigate the relationship between teachers’ readiness and the implementation of change in academic settings in the post-COVID era. The concept of teachers’ readiness is widely used, particularly during the change of curriculum setting since the COVID-19 pandemic. Readiness involves the preparation of as big as an organisation and as small as one person related to their beliefs, attitudes, and intentions regarding the need and the capacity to respond to change. However, facing a sudden change that happens without notice may not generate the intended outcomes. Getting ‘ready’ involves the transformation of individual needs physically and cognitively so that a person has control over and is capable of responding to the change. This study aimed to investigate individual and organisational factors in embracing change in an academic setting. As an effort to unravel the relationship between the concept of readiness and change, the focus of this article is to examine the perception of teachers’ readiness for online teaching and learning in higher institutions for post-COVID classroom settings. The study applied qualitative research design by interviewing five lecturers who have undergone the teaching process during the COVID-19 pandemic and proceeding with their services after the pandemic. The findings from the analyses stated that the aspect of self-efficacy and infrastructure contribute to teachers’ readiness for curriculum shifting after the pandemic.